Bisphenol A Promotes the Progression of Colon Cancer Through Dual-Targeting of NADPH Oxidase and Mitochondrial Electron-Transport Chain to Produce ROS and Activating HIF-1α/VEGF/PI3K/AKT Axis - Xia, Tianyi; Guo, Junnan; Zhang, Bomiao; Song, Chengxin; Zhao, Qunye; Cui, Binbin; Liu, Yanlong (Frontiers in Endocrinology, 2022)
Abstract Bisphenol A (BPA) is a high-production-volume industrial chemical. Despite recent research conducted on its carcinogenicity, its role in the development of colon cancer (CC) has been rarely studied. This study aims to evaluate the effects of BPA on the migration and invasion of CC cells. First, we clinically verified that patients with CC exhibit higher serum BPA level than healthy donors. Subsequently, different CC cell lines were exposed to a series of BPA concentrations, and the migration and invasion of cells were detected by the wound healing test and transwell assay. Finally, N-acetyl-L-cysteine (NAC) and siHIF-1α intervention was used to explore the effects of ROS and HIF-1α on cell migration and invasion, respectively. The results demonstrated that the occurrence of BPA-induced migration and invasion were dependent on the dose and time and was most pronounced in DLD1 cells. ROS production was jointly driven by NADPH oxidase (NOX) and mitochondrial electron-transport chain (ETC). Furthermore, the intervention of NAC and siHIF-1α blocked the HIF-1α/VEGF/PI3K/AKT axis and inhibited cell migration and invasion. In conclusion, our results suggest that BPA exposure promotes the excessive production of ROS induced by NOX and ETC, which in turn activates the HIF-1α/VEGF/PI3K/AKT axis to promote the migration and invasion of CC cells. This study provides new insights into the carcinogenic effects of BPA on CC and warns people to pay attention to environmental pollution and the harm caused to human health by low-dose BPA.